Glucocorticoids and Sarcoidosis: A Longitudinal Study on the Effects on Cortical and Trabecular Bone - Brismar, T.B.; Shams, Sara; Berinder, K.; Berlin, M.; Uddén, J.; Brismar, K.; Ringertz, H.G. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background:Glucocorticoid induced osteoporosis is a well-known side effect of glucocorticoid treatment. In sarcoidosis the impact on bone by glucocorticoid treatment is complex due to hormonal disturbances of calcium and vitamin-D, which by itself may cause bone loss. In this study we aimed to investigate the longitudinal impact of glucocorticoids on cortical and trabecular bone in patients with mild, recently diagnosed sarcoidosis. Methods: Ten patients (8 females; mean age 44 (±13)) were studied during one year of glucocorticoid treatment. The assessment of mainly cortical to purely trabecular bone was made by dual X-ray absorptiometry (DXA) of the spine and hip, quantitative ultrasound of the calcaneus, and magnetic resonance relaxometry of the spine and calcaneus. Bone and hormonal measurements were performed at baseline, after 3, 6, and 12 months, and baseline, 3 weeks and 3 months, respectively. Results: DXA of the spine, decreased from baseline at 6 months (P=0.01). R2’ of the calcaneus decreased with time (B: -3.6;P=0.03). In the females (n=8) there was a significant decrease in DXA of the spine when comparing 3 months and 6 months (P=0.03), and 3 months and 12 months (P=0.02) and a decrease in R2’of the calcaneus from baseline to 12 months (P=0.01). There was no change in hormonal levels. Conclusion: Treatment of initial mild sarcoidosis with dose tapered glucocorticoid therapy only mildly affects the final trabecular and cortical bone and hormone levels. Dose tapering is an important part in glucocorticoid therapy, likely contributing to the mild effects on bone observed in this study.